ANALISA LIKUIDASI PERSEKUTUAN SETELAH PROSES REALISASI MENGGUNAKAN MS. ACCESS PROGRAMMING - Suhartono, - (www.bsi.ac.id, 2016)
Currently, there are many large companies in the world merge into a single company either through acquisitions or mergers to strengthen the competitiveness with other companies. There are many examples of giant companies that acquire other companies, such as recently the company Alibaba Group Holding Ltd. acquired the majority of Lazada Group. There is a lot of interest a company merged with another company. One was for the company to move forward and avoid liquidation. Liquidation is a state where the alliance was dissolved by completing obligations to creditors and divide the remaining assets to the owners. The main purpose of liquidation is to perform the maintenance and clearance on the bankruptcy estate. One of the underlying condition that is an ally liquidation bankruptcy. The liquidation process consists of two stages: the process of changing the existing wealth into cash, which is called the realization process and the process of repayment of debts to creditors and repayment of capital to the rest of the members of the so-called process of liquidation. In this stage to do is register and the accumulation of wealth and corporate debt, announced in the newspapers and the Official Gazette of the Republic of Indonesia regarding the plan of distribution of the proceeds of the liquidation, to make payments to creditors, and pay the remainder of the proceeds of liquidation to shareholders. Keyword: Liquidation Guild, Process Realization, Ms. Access Programming